Effects of intravenous dexmedetomidine on hyperbaric bupivacaine spinal anesthesia: A randomized study - Dinesh, Chilkunda N. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND AND OBJECTIVES: The present study was designed to evaluate the effect of intravenous dexmedetomidine on spinal anesthesia with 0.5% of hyperbaric bupivacaine. MATERIALS AND METHODS: One hundred American Society of Anesthesiologists (ASA) physical status I/II patients undergoing elective surgeries under spinal anesthesia were randomized into two groups of 50 each. Immediately after subarachnoid block with 3 ml of 0.5% hyperbaric bupivacaine, patients in group D received a loading dose of 1 μg/kg of dexmedetomidine intravenously by infusion pump over 10 min followed by a maintenance dose of 0.5 μg/kg/h till the end of surgery, whereas patients in group C received an equivalent quantity of normal saline. RESULTS: The time taken for regression of motor blockade to modified Bromage scale 0 was significantly prolonged in group D (220.7 ± 16.5 min) compared to group C (131 ± 10.5 min) (P < 0.001). The level of sensory block was higher in group D (T 6.88 ± 1.1) than group C (T 7.66 ± 0.8) (P < 0.001). The duration for two-dermatomal regression of sensory blockade (137.4 ± 10.9 min vs. 102.8 ± 14.8 min) and the duration of sensory block (269.8 ± 20.7 min vs. 169.2 ± 12.1 min) were significantly prolonged in group D compared to group C (P < 0.001). Intraoperative Ramsay sedation scores were higher in group D (4.4 ± 0.7) compared to group C (2 ± 0.1) (P < 0.001). Higher proportion of patients in group D had bradycardia (33% vs. 4%) (P < 0.001), as compared to group C. The 24-h mean analgesic requirement was less and the time to first request for postoperative analgesic was prolonged in group D than in group C (P < 0.001). CONCLUSION: Intravenous dexmedetomidine significantly prolongs the duration of sensory and motor block of bupivacaine spinal anesthesia. The incidence of bradycardia is significantly higher when intravenous dexmedetomidine is used as an adjuvant to bupivacaine spinal anesthesia. Dexmedetomidine provides excellent intraoperative sedation and postoperative analgesia.